(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Assessment of right ventricular systolic function using the FAC index in patients with heart failure secondary to hypertension at Thai Nguyen Central Hospital. Research objects and methods: A cross-sectional descriptive study was conducted on eighty patients with heart failure secondary to hypertension, who had been clinically evaluated using electrocardiograms and echocardiography. Right ventricular systolic function indices measured included Tricuspid Annular Plane Systolic Excursion (TAPSE) and Right Ventricular Fractional Area Change (RVFAC). The data were processed using Epidata 3.0 and SPSS 26.0 programs. Results: The results show that there were 49 patients (61.25%) with heart failure due to hypertension who had abnormal RVFAC, and 31 patients (38.75%) with abnormal TAPSE. Elevated pulmonary artery systolic pressure was found in 25 patients (31.25%). No correlation was found between right ventricular systolic function indices and estimated pulmonary artery systolic pressure. However, there was a strong correlation between the indices used to assess right ventricular function (FAC and TAPSE). Conclusions: There was no correlation between right ventricular systolic function indices and estimated pulmonary artery systolic pressure. However, there was a strong correlation between the indices used to assess right ventricular function (FAC and TAPSE) and left ventricular systolic function (EF).